2009
DOI: 10.1073/pnas.0900216106
|View full text |Cite|
|
Sign up to set email alerts
|

A distinct pool of phosphatidylinositol 4,5-bisphosphate in caveolae revealed by a nanoscale labeling technique

Abstract: Fig. 1. Labeling of the liposome. (A)Outline of the method. Cells were rapidly frozen, freeze-fractured, and evaporated with carbon (C) and platinum/carbon (Pt/C) in vacuum. The replica of the split membrane was digested with SDS to remove noncast molecules and labeled by GST-PH. Both the cytoplasmic and exoplasmic halves of the membrane were examined. (B) Labeling of small unilamellar liposome replicas. Freeze-fracture replicas of liposomes containing 95 mol % of phosphatidylcholine (PC) and 5 mol % of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
165
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 55 publications
(56 reference statements)
14
165
1
2
Order By: Relevance
“…Together these observations suggest that PtdSer may play a critical role in the formation and stabilization of caveolae. Consistent with this notion, electron microscopic (EM) studies revealed an enrichment of a PtdSerbinding probe in caveolae (22,23).…”
Section: Edited By Dennis R Voelkersupporting
confidence: 58%
“…Together these observations suggest that PtdSer may play a critical role in the formation and stabilization of caveolae. Consistent with this notion, electron microscopic (EM) studies revealed an enrichment of a PtdSerbinding probe in caveolae (22,23).…”
Section: Edited By Dennis R Voelkersupporting
confidence: 58%
“…Considering that IP 3 is the head group of PI(4,5)P 2 , IP 3 may compete with PI(4,5)P 2 for ARD binding 33 . Consistent with this notion, 4a-PDD-evoked currents through TRPV4 were suppressed by the addition of the longer acyl chains of PI(4,5)P 2 (diC8-PI(4,5)P 2 and diC16-PI(4,5)P 2 ), but were augmented by the addition of the shorter acyl chains of PI(4,5)P 2 (diC4-PI(4,5)P 2 ) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A likely explanation for these differences is that the various PI(4,5)P 2 sensors (PH domains, antibodies, KCNQ2/3 channels, and isotope labeling) have different sensitivities and different nonlinearities and may not monitor identical pools of PM PI(4,5)P 2 . There is also some evidence for signaling microdomains (55)(56)(57) and independent pools of PI(4,5)P 2 (58,59) in nanodomains (60,61), possibilities that remain controversial (62).…”
Section: Discussionmentioning
confidence: 99%